ANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF ASSAY OF AMIFOSTINE FOR INJECTION BY REVERSE PHASE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - BASHEER AHMAD.S; HARITHA PAVANI.K; SURESH BABU.U; HAIMA.R; SHIVAJI.K (International Journal of Pharma and Bio Sciences, 2013)
A simple, economic, selective, precise, and accurateReverse phase High Performance Liquid Chromatography method for analysis of Amifostine for injection, was developed and validated according to ICH guidelines. The quantification of the drug was carried out using Lunar C8, 250 mm X 4.6 mm, 5 mm columnor its equivalent in isocratic mode, with mobile phase compressing of Buffer: Methanol (72:28)the flow rate was 1.0ml/min and the detection was carried at 220 nm. The retention time for Amifostine for injection was found to be 4.5. The percent assay was found to be 97.3%. Proposed method was validated for precision, accuracy, linearity range, specificity and robustness.